Lithium carbon fluoride battery electrolyte and use thereof

CN122968321APending Publication Date: 2026-10-23DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510501647.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

研究资料公开Li/CFx电池放电过程中约有45.26%的化学能转化为热能,因此相较于其他种类锂离子电池,锂氟化碳电池放电过程中存在大量能量损失,以及潜在的热失控问题

Benefits of technology

[0018]根据本发明提供的所述的锂氟化碳电池,所述锂氟化碳电池运行过程中的放电倍率为0.01C~10C。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of batteries, and provides a lithium-carbon fluoride battery electrolyte additive and application thereof, the lithium-carbon fluoride battery electrolyte comprising: an organic solvent, a lithium salt and an aluminum salt; the mass percentage of the aluminum salt in the lithium-carbon fluoride battery electrolyte is below 50%; the organic solvent is selected from ester solvents and ether solvents; and the aluminum salt is an inorganic aluminum salt. The specific aluminum salt is added to the lithium-carbon fluoride battery electrolyte, the aluminum ion provided by the aluminum salt serves as a component of the electrolyte, can be embedded into a lithium fluoride crystal lattice in the discharging process of the lithium-carbon fluoride battery, forms a cation-doped high-entropy lithium fluoride, and the heat generated by the obtained lithium-carbon fluoride battery in the discharging process is also significantly smaller than that of a conventional lithium-carbon fluoride battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a lithium fluoride carbon battery electrolyte and its application. Background Technology

[0002] Compared to other primary lithium batteries (such as Li / SOCl2 and Li / MnO2 batteries), Li / CF x The battery exhibits the highest theoretical specific capacity. These high-energy-density batteries have broad application prospects in military, aerospace, and medical fields. Theoretically, when x=1, CF x Its specific capacity is as high as 865 mAh g -1 It is approximately twice that of a Li / SOCl2 primary battery.

[0003] In previous studies, researchers have devoted a great deal of effort to CF x Materials were improved. These efforts included research on CF. x Various preparation methods for materials, construction of highly conductive current collectors, and the application of CF x The cathode undergoes surface modification. However, according to thermodynamic laws, the crystallinity of lithium fluoride during the discharge process of lithium-carbon fluoride batteries has a significant impact on its heat generation. Typically, well-crystallized lithium fluoride has lower energy, thus its formation is often accompanied by a large amount of heat. Research data shows that approximately 45.26% of the chemical energy in Li / CFx batteries is converted into heat energy during discharge. Therefore, compared to other types of lithium-ion batteries, lithium-carbon fluoride batteries experience significant energy loss and potential thermal runaway during discharge. Summary of the Invention

[0004] This invention provides a lithium fluoride carbon battery electrolyte and its application. By adding a specific aluminum salt to the lithium fluoride carbon battery electrolyte, the aluminum ions provided by the salt, as a component of the electrolyte, can be embedded in the lithium fluoride lattice during the discharge process of the lithium fluoride carbon battery, forming cation-doped high-entropy lithium fluoride. This results in a lithium fluoride carbon battery that generates significantly less heat during discharge than traditional lithium fluoride carbon batteries.

[0005] In a first aspect, the present invention provides a lithium fluoride carbon battery electrolyte, comprising: an organic solvent, a lithium salt, and an aluminum salt; wherein the mass percentage of the aluminum salt in the lithium fluoride carbon battery electrolyte is less than 50%; The organic solvent is selected from ester solvents and ether solvents; The aluminum salt is an inorganic aluminum salt.

[0006] The aluminum salt in this invention provides aluminum ions that, as a component of the electrolyte, can be embedded into the lithium fluoride lattice during the discharge process of a lithium fluoride battery, forming cation-doped high-entropy lithium fluoride. Compared to adding other cations, the lithium fluoride battery discharge product obtained under the action of aluminum ions, i.e., aluminum ion-doped lithium fluoride, has the highest entropy value. Correspondingly, the heat generated by the resulting lithium fluoride battery during discharge is significantly less than that of a conventional lithium fluoride battery.

[0007] The reason for selecting a mixture of ester and ether solvents as the electrolyte in this invention is that, according to quantum chemical calculations, aluminum ions tend to be distributed between the ester and ether groups in the lithium-ion solvation structure, forming a "lithium-ether-aluminum-ester" solvation structure. Only this solvation structure can ensure the formation of the cation-doped high-entropy lithium fluoride proposed in this invention, thereby improving the battery heating process. Furthermore, to ensure the stability of the solvation structure, inorganic aluminum salts, which are more easily dissociated from anionic groups, were chosen as additives. If organic aluminum salts were used, the battery heating process would not be improved because a suitable solvation structure could not be formed.

[0008] In the lithium fluoride carbon battery electrolyte provided by the present invention, the aluminum salt is selected from at least one of aluminum nitrates, aluminum chlorides, and aluminum sulfates.

[0009] According to the lithium fluoride carbon battery electrolyte provided by the present invention, the ester solvent is selected from at least one of dimethyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, and methyl ethyl carbonate.

[0010] According to the lithium fluoride carbon battery electrolyte provided by the present invention, the ether solvent is selected from at least one of ethylene glycol dimethyl ether, tetrahydrofuran, 1,2-dimethoxyethylene, 1,4-dioxocyclohexane, diethylene glycol dimethyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0011] In the lithium fluoride carbon battery electrolyte provided by the present invention, the volume ratio of the ester solvent to the ether solvent is 0.01~100:1.

[0012] In the lithium fluoride carbon battery electrolyte provided by the present invention, the aluminum salt accounts for 0.01 to 50% of the total mass of the lithium fluoride carbon battery electrolyte.

[0013] In the lithium fluoride carbon battery electrolyte provided by the present invention, the mass of aluminum salt accounts for 1 to 10% of the total mass of the lithium fluoride carbon battery electrolyte.

[0014] According to the lithium fluoride carbon battery electrolyte provided by the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, and lithium hexafluoroarsenate.

[0015] According to the lithium fluoride carbon battery electrolyte provided by the present invention, the molar concentration of the lithium salt in the lithium fluoride carbon battery electrolyte is 0.01~10M.

[0016] Secondly, the present invention also provides a lithium fluorinated carbon battery, the lithium fluorinated carbon battery comprising a positive electrode, a negative electrode, a separator and an electrolyte; The electrolyte is selected from the lithium fluoride carbon battery electrolytes described above.

[0017] According to the lithium fluoride carbon battery provided by the present invention, the operating temperature of the lithium fluoride carbon battery is -40℃ to 150℃.

[0018] According to the lithium fluoride carbon battery provided by the present invention, the discharge rate of the lithium fluoride carbon battery during operation is 0.01C~10C.

[0019] This invention provides a lithium fluoride carbon battery electrolyte and its application. By adding a specific aluminum salt to the lithium fluoride carbon battery electrolyte, the aluminum ions provided by the salt, as a component of the electrolyte, can be embedded in the lithium fluoride lattice during the discharge process of the lithium fluoride carbon battery, forming cation-doped high-entropy lithium fluoride. This results in a lithium fluoride carbon battery that generates significantly less heat during discharge than traditional lithium fluoride carbon batteries. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0021] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.

[0022] Example 1A: Lithium-ion fluorinated carbon battery electrolyte A lithium fluorinated carbon battery electrolyte, the preparation process of which is as follows: Dimethyl carbonate, propylene carbonate, and ethylene glycol dimethyl ether were mixed evenly in a volume ratio of 1:1:1. 1 L of the mixed solvent was weighed out, and 1 mol of LiClO4 was added and stirred to dissolve. Aluminum nitrate was then added to the mixture at 2.5% of the electrolyte mass, and stirring was continued to dissolve the mixture to obtain the lithium fluoride carbon battery electrolyte.

[0023] Example 2A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that aluminum nitrate is replaced with an equal percentage of aluminum chloride by mass.

[0024] Example 3A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that the amount of aluminum nitrate added is 10% of the electrolyte mass.

[0025] Example 4A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that the amount of aluminum nitrate added is 1% of the electrolyte mass.

[0026] Example 5A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that the amount of aluminum nitrate added is 0.01% of the electrolyte mass.

[0027] Example 6A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that the amount of aluminum nitrate added is 50% of the electrolyte mass.

[0028] Example 7A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that 1L of mixed solvent is replaced by a 1:1 mixture of dimethyl carbonate and ethylene glycol dimethyl ether.

[0029] Example 8A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that 1L of mixed solvent is replaced by a 1:9 mixture of dimethyl carbonate and ethylene glycol dimethyl ether.

[0030] Example 9A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that 1L of mixed solvent is replaced by an equal volume of a 9:1 mixture of dimethyl carbonate and ethylene glycol dimethyl ether.

[0031] Example 10A: Lithium-ion fluorinated carbon battery electrolyte It is basically the same as Example 1, except that 1L of mixed solvent is replaced by an equal volume of a mixed solvent of dimethyl carbonate, 1,2-dimethoxyethylene and ethylene glycol dimethyl ether in a 1:1:1 ratio.

[0032] Example 1B Lithium-ion Fluoride Battery A method for preparing a lithium fluoride carbon battery, the process of which is as follows: (1) Fluorocarbon, conductive carbon black and PVDF (polyvinylidene fluoride) are dissolved in N-methylpyrrolidone in a mass ratio of 8:1:1 and mixed evenly. The mixture is then coated into an electrode film with a thickness of 0.15 mm using a wet film preparation device. After vacuum drying, the film is cut into electrode sheets with a diameter of 14 mm using a slicer. The weight of the active material is then weighed and the mass of the active material is calculated.

[0033] (2) Using lithium sheet as negative electrode and Celgard 2500 as separator, 70 μL of lithium fluoride carbon battery electrolyte prepared in Example 1 was added and assembled into a button cell in a glove box filled with argon gas.

[0034] Examples 2B~10B: Lithium-carbon fluoride batteries This is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an equal volume of the lithium fluoride carbon battery electrolyte prepared in Examples 2-6. The specific correspondence is shown in Table 1 below.

[0035] Table 1

[0036] Comparative Example 1 Battery It is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an electrolyte prepared in the following manner with an equal volume.

[0037] The electrolyte in this comparative example is basically the same as that in Example 1, except that aluminum nitrate is not added.

[0038] Comparative Example 2 Battery It is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an electrolyte prepared in the following manner with an equal volume.

[0039] The electrolyte in this comparative example is basically the same as that in Example 1, except that the amount of aluminum nitrate added is 70% of the electrolyte mass.

[0040] Comparative Example 3 Battery A battery is prepared in a manner similar to that of Example 1B, except that aluminum nitrate and carbon fluoride are added together to the electrode membrane in step (1), and the amount of aluminum nitrate added is the same as the mass of aluminum nitrate in the electrolyte in step (2) of Example 1B. Meanwhile, no aluminum nitrate is added to the electrolyte in step (2).

[0041] Comparative Example 4 Battery It is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an electrolyte prepared in the following manner with an equal volume.

[0042] The electrolyte in this comparative example is basically the same as that in Example 1, except that aluminum nitrate is replaced with an equal percentage of aluminum acetate by mass.

[0043] Comparative Example 5 Battery It is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an electrolyte prepared in the following manner with an equal volume.

[0044] The electrolyte in this comparative example is basically the same as that in Example 1, except that aluminum nitrate is replaced with gallium nitrate of equal mass percentage.

[0045] Comparative Example 6 Battery It is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an electrolyte prepared in the following manner with an equal volume.

[0046] The electrolyte in this comparative example is basically the same as that in Example 1, except that dimethyl carbonate and propylene carbonate are not added.

[0047] Comparative Example 7 Battery It is basically the same as Example 1B, except that the electrolyte prepared in Example 1 is replaced by an electrolyte prepared in the following manner with an equal volume.

[0048] The electrolyte in this comparative example is basically the same as that in Example 1, except that ethylene glycol dimethyl ether is not added.

[0049] Test Example 1 Electrochemical and temperature tests were conducted on the batteries used in the examples and comparative examples. Specifically, the electrochemical tests were performed on the assembled flow-type supercapacitor using a Landian constant current charge-discharge instrument. The equipment used was a CT2001A battery testing system manufactured by Wuhan Landian Electronics Co., Ltd. During the electrochemical tests, the battery was discharged at a 5C rate to 1V. For the battery positive electrode casing temperature test, a temperature sensor was attached to the center of the positive electrode side of the coin cell to sense temperature changes. During the test, the battery discharge capacity and the surface temperature of the positive electrode casing at the moment of discharge completion were recorded.

[0050] The discharge specific capacity and positive electrode casing temperature of the batteries in the above embodiments and comparative examples were detected during electrochemical testing, as shown in Table 2 below.

[0051] Table 2

[0052] Test Example 2 The phase characterization of lithium fluoride, the discharge product obtained after electrochemical testing of the lithium-carbon fluoride batteries in the examples and comparative examples, was performed using X-ray diffraction (XRD). The test conditions were: Cu-Kα target, wavelength λ = 1.54 Å, tube voltage 40 kV, tube current 40 mA, scan range 2θ = 10–90°, and scan speed 10 min. -1 The cathode material after discharge was tested under the following conditions.

[0053] The XRD results were analyzed as follows: The three strongest peaks of crystalline lithium fluoride are located at 2θ = 38.7°, 45.0°, and 65.5° (corresponding to the (111), (200), and (220) crystal planes of LiF, respectively), while high-entropy lithium fluoride is in an amorphous state, and the XRD test results are relatively smooth without any obvious diffraction peaks. The analysis results are shown in Table 3 below.

[0054] Table 3

[0055] As can be seen from Comparative Example 2, during the preparation of the fluorinated carbon electrode, the specific capacity of the assembled coin cell decreased significantly and a large amount of heat was generated during discharge. This was because the amount of aluminum nitrate added to the electrolyte was too high and not fully dissolved (the local aluminum nitrate concentration between the positive electrodes was too high, and the aluminum nitrate solution was in a supersaturated state, etc.), which increased the internal resistance between the active materials of the electrode, ultimately leading to a large amount of heat generated during battery discharge.

[0056] As can be seen from Comparative Example 3, during the preparation of the fluorinated carbon electrode, the specific capacity of the assembled coin cell decreased significantly and a large amount of heat was generated during discharge. This is because the aluminum nitrate was not fully dissolved in the initial stage of discharge (the local aluminum nitrate concentration between the positive electrodes was too high, and the aluminum nitrate solution was in a supersaturated state, etc.), which increased the internal resistance between the active materials of the electrode, ultimately leading to a large amount of heat generated during the discharge of the battery.

[0057] As shown in Comparative Example 4, the specific capacity of the assembled coin cell decreased significantly and a large amount of heat was generated during discharge during the preparation of the fluorinated carbon electrode. This is because the dissociation energy of chloride ions and organic groups (here referring to acetate groups) in organoaluminum is relatively large. The aluminum element in the electrolyte cannot fully dissociate from the acetate group, resulting in the inability to form a stable "lithium-ether-aluminum-ester" solvation structure, and thus the inability to obtain high-entropy lithium fluoride products. Consequently, the heating process and heat generation of the battery cannot be improved.

[0058] As can be seen from Comparative Example 5, during the preparation of fluorinated carbon electrodes, the specific capacity of the assembled coin cells decreased significantly and a large amount of heat was generated during discharge. This is because the outer electronic structure of gallium nitrate cannot play the same role as the solvation structure of "lithium-ether-aluminum-ester", and high-entropy lithium fluoride products cannot be obtained, thus failing to improve the battery heating process and heat generation.

[0059] As can be seen from Comparative Examples 6 and 7, the specific capacity of the assembled coin cell decreased significantly during the preparation of the fluorinated carbon electrode and a large amount of heat was generated during discharge. This is because the solvent system in the electrolyte cannot form a "lithium-ether-aluminum-ester" solvation structure, and high-entropy lithium fluoride products cannot be obtained, thus failing to improve the battery heating process and heat generation.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium fluoride carbon battery electrolyte, characterized in that, include: Organic solvent, lithium salt, and aluminum salt; the mass percentage of aluminum salt in the lithium fluoride carbon battery electrolyte is less than 50%; The organic solvent is selected from ester solvents and ether solvents; The aluminum salt is an inorganic aluminum salt.

2. The lithium fluoride carbon battery electrolyte according to claim 1, characterized in that, The aluminum salt is selected from at least one of aluminum nitrates, aluminum chlorides, and aluminum sulfates.

3. The lithium fluoride carbon battery electrolyte according to claim 1 or 2, characterized in that, The ester solvent is selected from at least one of dimethyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, and methyl ethyl carbonate; And / or, the ether solvent is selected from at least one of ethylene glycol dimethyl ether, tetrahydrofuran, 1,2-dimethoxyethylene, 1,4-dioxane, diethylene glycol dimethyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

4. The lithium fluoride carbon battery electrolyte according to any one of claims 1 to 3, characterized in that, The volume ratio of the ester solvent to the ether solvent is 0.01 to 100:

1.

5. The lithium fluoride carbon battery electrolyte according to any one of claims 1 to 4, characterized in that, The aluminum salt accounts for 0.01 to 50% of the total mass of the lithium fluoride carbon battery electrolyte; preferably, the aluminum salt accounts for 1 to 10% of the total mass of the lithium fluoride carbon battery electrolyte.

6. The lithium fluoride carbon battery electrolyte according to any one of claims 1 to 5, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxaborate, lithium difluorooxaborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, and lithium hexafluoroarsenate.

7. The lithium fluoride carbon battery electrolyte according to any one of claims 1 to 6, characterized in that, The molar concentration of the lithium salt in the lithium fluoride carbon battery electrolyte is 0.01~10M.

8. A lithium fluoride carbon battery, characterized in that, The lithium fluoride carbon battery includes a positive electrode, a negative electrode, a separator, and an electrolyte; The electrolyte is selected from the lithium fluoride carbon battery electrolyte according to any one of claims 1 to 7.

9. The lithium fluoride carbon battery according to claim 8, characterized in that, The operating temperature of the lithium fluoride carbon battery is -40℃ to 150℃.

10. The lithium fluoride carbon battery according to claim 8 or 9, characterized in that, The discharge rate of the lithium fluoride carbon battery during operation is 0.01C~10C.